2022
DOI: 10.3389/fendo.2022.952055
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilium in kidney development, function and disease

Abstract: The primary cilium is a hair-like, microtubule-based organelle that is covered by the cell membrane and extends from the surface of most vertebrate cells. It detects and translates extracellular signals to direct various cellular signaling pathways to maintain homeostasis. It is mainly distributed in the proximal and distal tubules and collecting ducts in the kidney. Specific signaling transduction proteins localize to primary cilia. Defects in cilia structure and function lead to a class of diseases termed ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“…In humans, they showed that the number of ciliated cells and the length of cilia are positively correlated with the diabetic kidney disease class in the kidney biopsies of the patients with diabetic kidney disease. These results are consistent with those of STZ-injected mice and db/db mice ( 6 ). The researchers speculated that HDAC6-dependent tubulin deacetylation was inhibited in renal tubular epithelial cells in diabetic kidney disease ( 6 ).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In humans, they showed that the number of ciliated cells and the length of cilia are positively correlated with the diabetic kidney disease class in the kidney biopsies of the patients with diabetic kidney disease. These results are consistent with those of STZ-injected mice and db/db mice ( 6 ). The researchers speculated that HDAC6-dependent tubulin deacetylation was inhibited in renal tubular epithelial cells in diabetic kidney disease ( 6 ).…”
supporting
confidence: 92%
“…These results are consistent with those of STZ-injected mice and db/db mice ( 6 ). The researchers speculated that HDAC6-dependent tubulin deacetylation was inhibited in renal tubular epithelial cells in diabetic kidney disease ( 6 ). They also suggested that aberrant ciliogenesis may influence mitochondrial biogenesis and fatty acid β oxidation, accelerating renal fibrosis.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we utilized ciliary length as a phenotypic read-out assay to identify cell types of genetic interactions between Pkd1 and Fbxw7 across different kidney tubules. Notably, ciliary length is a sensitive measure, particularly relevant during postnatal development and in the context of ADPKD 31 . We found a significant elongation of primary cilia in epithelial cells of proximal tubules of UbcCre ERT2 ;Pkd1 f/f animals, whereas UbcCre ERT2 ;Pkd1 f/f ;Fbxw7 f/f animals exhibited a normalization of ciliary length.…”
Section: Resultsmentioning
confidence: 99%
“…Polcystin-1 (encoded by PKD1 gene) and polycystin-2 (encoded by PKD2 gene) form a transmembrane complex and are located in the primary cilia functioning as a calcium channel, which can sense external stimuli such as growth factors, chemical or mechanic stress (6). Mutations in ciliary genes responsible for the assembly of primary cilia (such as kinesin family member 3A, KIF3A) can also induce cystogenesis in mouse kidneys (7). Accumulating evidence show that ciliary proteins are implicated in the development or disease condition of other organs, for example, bone development and blood pressure control (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%